2022
DOI: 10.1002/oby.23502
|View full text |Cite
|
Sign up to set email alerts
|

Pragmatic implementation of a fully automated online obesity treatment in primary care

Abstract: ObjectiveBehavioral obesity treatment implemented in primary care is efficacious but typically involves face‐to‐face or phone contact. This study evaluated enrollment, engagement, and 12‐week weight loss in a fully automated online behavioral weight‐loss intervention implemented pragmatically in a primary care network.MethodsAs part of routine primary care, providers and nurse care managers offered a no‐cost online obesity treatment program to 1,721 patients. Of these, 721 consented and were eligible (aged 18‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
2
3
0
Order By: Relevance
“…Compared with other stand-alone digital weight loss interventions, the magnitude of weight loss found in our study was comparable with many studies [ 10 , 25 , 27 , 29 , 36 , 99 ], higher than some [ 26 , 41 , 42 , 100 ], and lower than a recent fully automated, large-scale pragmatic trial comprising mostly non-Hispanic White participants [ 101 ]. This is an important area of research, as many barriers exist to attending in-person treatment, such as living far from a medical clinic or treatment program [ 102 ], having childcare or caregiver responsibilities, or having fluctuating working schedules.…”
Section: Discussionsupporting
confidence: 88%
“…Compared with other stand-alone digital weight loss interventions, the magnitude of weight loss found in our study was comparable with many studies [ 10 , 25 , 27 , 29 , 36 , 99 ], higher than some [ 26 , 41 , 42 , 100 ], and lower than a recent fully automated, large-scale pragmatic trial comprising mostly non-Hispanic White participants [ 101 ]. This is an important area of research, as many barriers exist to attending in-person treatment, such as living far from a medical clinic or treatment program [ 102 ], having childcare or caregiver responsibilities, or having fluctuating working schedules.…”
Section: Discussionsupporting
confidence: 88%
“…In the per-protocol analysis of maintenance-engaged participants, the number of lessons viewed was low (most often, 3 of 9 lessons), replicating findings from prior studies . As our group reported in a previous study, during the treatment phase, participants in the trial viewed 6.5 of the first 12 videos, and 37% of participants watched all 12 initial lessons, suggesting a decline in engagement over time that is common in online interventions . Nevertheless, participants who watched more lessons or self-monitored on more days had better long-term weight losses.…”
Section: Discussionsupporting
confidence: 79%
“…In the per-protocol analysis with 273 participants who engaged with the maintenance intervention, mean weight loss was 6.19 kg at 3 months, suggesting that these engaged participants likely adhered better to initial treatment recommendations and thus achieved better weight losses than unengaged participants. These outcomes are similar to the 3-month weight loss of 5.1 kg reported in our previous analysis of self-reported weight change that included only participants who engaged with the initial 3-month RxWL intervention . As in the intention-to-treat analysis, the per-protocol analysis showed that participants in the refresher and monthly maintenance groups better maintained their weight loss than those in the newsletter control maintenance group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More frequent meetings do not appear necessary to induce a 15–20% weight loss with the new AOMs, and some visits likely can be conducted by telephone or video-conferencing without loss of efficacy [ 31 , 99 ]. Asynchronous, digitally delivered programs, which involve minimal person-to-person contact, also are likely to be explored [ 100 ]. In traditional office practice, RDs initially would appear to be best prepared to provide lifestyle counseling, but a variety of primary care professionals including physicians, nurse practitioners, nurses, psychologists, and medical assistants have provided such care following a structured behavioral protocol [ 12 ].…”
Section: Behavioral and Psychosocial Issues Including Terminating Aomsmentioning
confidence: 99%